MODERASI BERAGAMA MELALUI PENERAPAN TEOLOGI KERUKUNAN - Komang Heriyanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Religious moderation is our perspective in moderate religion, which is to understand and practice religious teachings in not extreme way. To minimize religious conflict, religious moderation is the solution. Religious moderation can be realized by applying theology of harmony. Theology of harmony is how each religious adherent comprehends the religion that they believes in comprehensively and then seeks to find common ground in the values of other religions, not in the domain of religious beliefs they wants to unite, what they wants to unite are the values of togetherness not the values of the differences. Harmony among religions is one of the main sticks in maintaining good, peaceful, united and agreed relations between religious communities of different religions to live in harmony.Keywords: Religious Moderation, Theology of Harmony.